Analysis of a Model for The Development of Sharia Cooperatives in Central Tapanuli Regency: The Analytic Network Process Method - Muhammad Rahman; Rukiah Rukiah; Fatahuddin Aziz Siregar (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
Sharia cooperatives play a strategic role in promoting equitable economic growth, particularly in Central Tapanuli Regency. However, their development still faces various challenges, such as low-quality human resources, weak institutional governance, limited capital, as well as insufficient regulatory support and competitiveness compared to other financial institutions. This study aims to analyze models for the development of Islamic cooperatives and determine effective strategic priorities to improve their performance. The study employs a mixed-methods approach using the Analytic Network Process (ANP) method. Data were collected through in-depth interviews and paired-comparison questionnaires involving experts, regulators, and cooperative managers. The results indicate that internal factors are the primary constraints, with a dominant focus on human resources, particularly managerial capabilities and understanding of Sharia principles. Meanwhile, external factors such as competitors and regulatory support also influence the development of the cooperatives. The implications of this study underscore the importance of strengthening human resource capacity through continuous training and adaptive policy support to enhance the competitiveness and sustainability of Islamic cooperatives.